2020
DOI: 10.1177/1350650120920502
|View full text |Cite
|
Sign up to set email alerts
|

A novel passive filtration system for splash-lubricated gearboxes: Part 1

Abstract: Splash-lubricated gearboxes are widely used in many industries. Contaminant removal systems are rarely employed in splash-lubricated gearboxes, such as some gearboxes are used in helicopters and mining machines. The maintenance of lubrication systems in those machines relies on periodic onsite inspection and lubricant change. However, wear debris generated during operation will suspend in lubricant and cause damage to contacting surfaces of gearbox’s components. In this first part of a two-part paper, a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…It is found that after the helicopter has landed on the ground for a few hours, most of the wear particles suspended in lubricant tend to settle to the bottom of the oil sump. Lubricant temperature will also gradually decrease to the ambient temperature [6]. At room temperature, the SMA wires with shape memory effects are in martensite phase and they are relatively softer than the superelastic SMA wires.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that after the helicopter has landed on the ground for a few hours, most of the wear particles suspended in lubricant tend to settle to the bottom of the oil sump. Lubricant temperature will also gradually decrease to the ambient temperature [6]. At room temperature, the SMA wires with shape memory effects are in martensite phase and they are relatively softer than the superelastic SMA wires.…”
Section: Introductionmentioning
confidence: 99%